Climatological analysis of cyclone tracks in the Western Mediterranean - Dario Hourngir; Massimiliano Burlando; Djordje Romanic (2023)
Cyclones are the main weather patterns in the mid-latitude climates. They are often associated with heavy precipitation and wind extremes. A detailed knowledge of their source and path—namely, the cyclonic tracks—as well as their modification due to anthropogenic effects or climate variability are fundamental in forecasting weather and determining future impacts on regional climates. Over the last decades, several objective methods for cyclone detection and tracking have been implemented. Each of them is based on different dynamics or numerical techniques. For this work, we chose the Melbourne University cyclone finding and tracking scheme, which uses a quasi-Lagrangian framework, originally developed for the Southern Hemisphere, but equally accurate for the Northern Hemisphere to investigate the kinematics and dynamics features of the western Mediterranean cyclones. The input dataset consists of the ERA5 reanalyses of mean sea level pressure on a 0.25° × 0.25° regular latitude-longitude grid. This dataset was used to perform the analysis on a domain between 315°W–25°E and 25°N–60°N in order to take into account the development of cyclones in the early stages of their lifetime over the Atlantic Ocean that can affect the central and western parts of the Mediterranean Sea. The study compares the algorithm outcomes with the time series of some relevant climatological teleconnection indexes, such as the North Atlantic Oscillation (NAO) and the Western Mediterranean oscillation (WeMO), to identify possible trends and correlations between them.